Preparation method and application of barium titanate powder
Through the combination of sand milling and high-energy ball milling, the barium titanate raw material is refined to form barium titanate micronucleus, which solves the problems of high cost and uneven grains in the preparation of barium titanate powder, and is suitable for miniaturization and multi-dimensional Ultrafine barium titanate powder of ceramic capacitor.
Patent Information
- Application Number
- CN202411475252.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-03
AI Technical Summary
In the existing barium titanate powder preparation method, the liquid phase method has high cost and hydroxyl defects in the dielectric layer. The high calcining temperature of the solid phase method leads to large grain size and poor uniformity, making it difficult to meet the miniaturized multi-layer ceramic capacitors. need.
The method of combining sand milling and high-energy ball milling is used to refine the raw materials through mechanical shearing to form barium titanate micronuclei, improve dispersion and uniformity, and reduce the calcination temperature to obtain ultrafine barium titanate powder.
It realizes the preparation of barium titanate powder with low cost, good dispersion and uniform grains, and is suitable for the production of miniaturized high-end multi-layer ceramic capacitors.
Smart Images

Figure BDA0005095913620000071 
Figure BDA0005095913620000081 
Figure BDA0005095913620000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic materials, and in particular relates to a preparation method of barium titanate powder and application thereof. Background Art
[0002] Barium titanate (BaTiO3) is the most important ceramic raw material in multilayer ceramic capacitors (MLCC). As MLCC continues to develop towards miniaturization, high capacitance, high reliability and low cost, in order to meet the strict restriction of dielectric layer thickness <1μm, ensure the reliability of product performance and reduce production costs, it is urgent to develop a low-cost, well-dispersed and uniformly grained ultrafine BaTiO3 powder.
[0003] At present, the preparation methods of barium titanate powder are mainly divided into two categories: liquid phase method and solid phase method. The powder prepared by the liquid phase method has good dispersibility and uniform particle size, but the production cost is high and the process equipment is complicated. In addition, hydroxyl defects are very likely to exist in the powder prepared by the liquid phase method, which reduces the reliability of MLCC products and does not meet the use requirements of high-reliability MLCC products. The solid phase method is a classic powder preparation method. It uses cheap barium carbonate and titanium dioxide as raw materials, and synthesizes barium titanate powder after mixing, grinding, drying and calcining. It has the advantages of low cost, simple operation, high output and few grain defects. However, due to the high calcination temperature of the solid phase process, the prepared barium titanate powder has the disadvantages of large grain size, poor uniformity and poor dispersibility, which hinders the application of solid phase barium titanate powder in miniaturized MLCC products. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a method for preparing barium titanate powder.
[0005] A second object of the present invention is to provide a multilayer ceramic capacitor.
[0006] The third object of the present invention is to provide the application of the preparation method of the above-mentioned barium titanate powder in the preparation of ceramic products.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a method for preparing barium titanate powder, comprising the following steps:
[0009] S1: grinding the raw materials including the barium source, the titanium source and the solvent with a grinding ball A at a grinding speed of 600 to 1000 rpm for 15 to 30 hours to obtain a primary slurry;
[0010] S2: heating the primary slurry to 40-100° C. and keeping the temperature for 2-10 hours;
[0011] S3: high-energy ball milling at a speed of 1000-1400 rpm for 0.5-3 h using grinding ball B to obtain a secondary slurry;
[0012] S4: calcining the secondary slurry to obtain the barium titanate powder;
[0013] In the step S1, the ratio of the total mass of the barium source and the titanium source to the mass of the grinding ball A is 1:(1-6);
[0014] In the step S3, the ratio of the total mass of the barium source and the titanium source to the mass of the grinding ball B is 1:(3-6).
[0015] The present invention adopts sand milling and high-energy ball milling in combination, both of which refine the size of the raw materials (i.e., titanium source and barium source) through mechanical shearing, increase the specific surface area and stored energy of the raw materials, and the refined raw materials have more high-energy sites, and the high-energy sites are potential sites for nucleation of barium titanate crystals during calcination, which are conducive to the formation of barium titanate fine crystals (micronuclei) at a lower temperature. The rotation speed and grinding time of the sand milling and high-energy ball milling in the present invention are conducive to the activation and dispersion of the raw materials, but when the raw materials reach the optimal grinding state, the rotation speed of the sand milling / high-energy ball milling is too fast and the time is too long, and the specific surface energy of the raw materials continues to increase, which will lead to the reverse grinding phenomenon, the raw materials agglomerate with each other, and the dispersion effect becomes worse; while the rotation speed of the sand milling / high-energy ball milling is too slow and the time is too short, which will lead to a slow grinding efficiency, weaken the mechanical shear force provided, and cause the raw material grinding effect to become worse, and the particle size decreases slowly, resulting in a larger particle size of the powder after grinding, which is not conducive to obtaining a barium titanate powder with a high c / a value and uniform particles.
[0016] In step S1 of the present invention, the sanding speed is 600-1000 rpm, for example, can be selected from 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm, 1000 rpm. Preferably, the sanding speed is 700-900 rpm.
[0017] In step S1 of the present invention, the sanding time is 15 to 30 hours, for example, can be selected from 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours, 30 hours. Preferably, the sanding time is 20 to 25 hours.
[0018] In step S2 of the present invention, the heating temperature is 40-100° C., for example, can be selected from 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C. Preferably, the heating temperature is 80-100° C.
[0019] In step S2 of the present invention, the insulation time is 2 to 10 hours, for example, can be selected from 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours. Preferably, the insulation time is 2 to 4 hours.
[0020] The sand milling step in step S1 makes the high-energy sites formed by the raw materials conducive to the formation of barium titanate micronuclei during the heating and insulation process, but if the heating temperature is too high, the formation rate of the barium titanate micronuclei will be accelerated, which is not conducive to controlling the progress of the reaction and the particle uniformity will deteriorate; if the insulation time is too long, the already formed barium titanate micronuclei will grow slowly, forming broken crystals in the subsequent high-energy ball milling process, the powder particle uniformity will deteriorate, and the c / a value will decrease; if the heating temperature is too low and the insulation time is too short, there will be no improvement in the uniformity of the calcined powder particles.
[0021] In step S3 of the present invention, the rotation speed during high energy ball milling is 1000-1400 rpm, for example, it can be selected from 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm. Preferably, the rotation speed during high energy ball milling is 1100-1200 rpm.
[0022] In step S3 of the present invention, the high energy ball milling time is 0.5 to 3 hours, for example, it can be selected from 0.5 hours, 0.7 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours. Preferably, the high energy ball milling time is 1 to 2 hours.
[0023] Compared with sand milling, high-energy ball milling can not only further refine the size of raw materials, but also help to form barium titanate micronuclei, thereby increasing the tetragonal phase content (c / a) and particle uniformity of the calcined powder.
[0024] In step S1 of the present invention, the ratio of the total mass of the barium source and the titanium source to the mass of the grinding ball A (i.e., the material-to-ball ratio) is 1:(1-6), for example, can be selected from 1:1, 1:2, 1:3, 1:4, 1:5, 1:6.
[0025] Preferably, the grinding ball A is selected from at least one of an alumina ball, a polyurethane ball, a steel ball, a zirconia ball, a nylon grinding ball, and a polytetrafluoroethylene grinding ball.
[0026] In step S3 of the present invention, the ratio of the total mass of the barium source and the titanium source to the mass of the grinding balls B (ie, the material-ball ratio) is 1:(3-6), for example, can be selected from 1:3, 1:4, 1:5, 1:6.
[0027] Preferably, the grinding ball B is selected from at least one of an alumina ball, a polyurethane ball, a steel ball, a zirconia ball, a nylon grinding ball, and a polytetrafluoroethylene grinding ball.
[0028] Preferably, the barium source is selected from at least one of barium carbonate, barium hydroxide octahydrate, barium oxide and barium chloride.
[0029] Preferably, the titanium source is selected from at least one of titanium dioxide and titanium tetrachloride.
[0030] Preferably, the solvent comprises water.
[0031] Preferably, the diameter of the grinding ball A is 0.3-1.0 mm, for example, can be selected from 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, and 1.0 mm.
[0032] Preferably, the diameter of the grinding ball B is 0.1-0.5 mm, for example, can be selected from 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm.
[0033] The inventors have found through extensive research that within the range of the material-ball ratio set in the present invention, a better grinding effect can be obtained. However, when the diameter of the grinding ball A / grinding ball B is larger and the material-ball ratio is higher, which is higher than the range of the present invention, the shear and collision frequencies provided during the grinding process are smaller, resulting in a poor ball milling effect on the raw materials, a large difference in the particle size of the raw materials after grinding, and a poor dispersion effect. When the diameter of the grinding ball A / grinding ball B is smaller and the material-ball ratio is lower, which is lower than the range of the present invention, the grinding efficiency within the same grinding time is poor, which is not conducive to improving production efficiency.
[0034] The sand milling in step S1 and the high-energy ball milling in step S3 of the present invention can provide a stronger mechanical shearing effect by adjusting the ball milling speed, time, diameter of grinding ball A / grinding ball B and material ball ratio, which helps to obtain a raw material mixed powder with a smaller particle size and more uniform dispersion. The high-energy ball milling process helps to form barium titanate micronuclei, and the uniformly distributed barium titanate micronuclei help to form barium titanate powder with good dispersion and uniform particle size during the calcination process.
[0035] Preferably, the molar ratio of barium in the barium source to titanium in the titanium source is (0.99-1.04):1, for example, can be selected from 0.99:1, 1.00:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1.
[0036] Preferably, the preparation raw materials also include a dispersant; the mass of the dispersant is 1 to 10% of the total weight of the barium source and the titanium source, for example, it can be selected from 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0037] Preferably, the dispersant is selected from at least one of polyacrylate, maleic anhydride, polyvinyl alcohol and tartrate.
[0038] Preferably, the step S4 is: drying the secondary slurry, sieving it, and then calcining it to obtain the barium titanate powder.
[0039] Preferably, the calcination temperature is 1000-1300°C, for example, can be selected from 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C.
[0040] Preferably, the calcination time is 0.5 to 3 h, for example, can be selected from 0.5 h, 0.8 h, 1 h, 1.5 h, 2 h, 2.5 h, and 3 h.
[0041] Preferably, the drying temperature is 80-100°C, for example, can be selected from 80°C, 85°C, 90°C, 95°C, 100°C.
[0042] Preferably, the drying time is 1 to 3 hours, for example, can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours.
[0043] Preferably, step S2 is heated in a water bath.
[0044] The second aspect of the present invention provides a multilayer ceramic capacitor comprising inner electrode layers and dielectric layers alternately stacked, wherein the dielectric layers are made of raw materials including barium titanate powder prepared by the preparation method described in the first aspect of the present invention.
[0045] Preferably, the dielectric layer has a thickness of less than 1 μm.
[0046] The third aspect of the present invention provides application of the method for preparing barium titanate powder according to the first aspect of the present invention in preparing ceramic products.
[0047] The beneficial effects of the present invention are as follows: the preparation method of the present invention firstly activates the barium source and the titanium source by sand milling to improve the reaction activity and dispersion degree of the titanium source and the barium source; then, a large number of barium titanate micronuclei are introduced onto the surface of the barium source by heating the primary slurry of the barium source and the titanium source after sand milling activation; and then, the strong mechanical shear force of high-energy ball milling is used to further improve the dispersion degree and uniformity of the barium titanate micronuclei and the raw materials in the slurry, thereby achieving uniform growth of barium titanate grains during the calcination process, and finally obtaining ultrafine barium titanate powder with uniform grains and high tetragonal phase content, which is then applied to the production of miniaturized high-end MLCC products. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 1 is a flow chart of the preparation process of barium titanate powder in an embodiment of the present invention. DETAILED DESCRIPTION
[0049] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0050] The preparation process flow chart of barium titanate powder in Examples 1 to 32 of the present invention is as follows Figure 1 shown.
[0051] Example 1
[0052] This example provides a method for preparing barium titanate powder, comprising the following steps:
[0053] (1) Weighing barium chloride powder and titanium dioxide powder in a Ba:Ti molar ratio of 1.05:1, then dispersing the powder in pure water and adding 5% of a polyacrylate dispersant relative to the total weight of the powder, mixing well and then sand grinding, the diameter of the grinding ball A used was 0.5 mm, the sand mill ball ratio (mass ratio of powder to grinding ball A) was 1:3, the sand milling speed was set to 800 rpm, and a primary slurry was obtained after sand grinding for 22 hours;
[0054] (2) keeping the obtained primary slurry in a water bath at 90° C. for 3 h, and then discharging the slurry to obtain a hydrothermal slurry;
[0055] (3) The hydrothermal slurry was subjected to high-energy ball milling. The diameter of the grinding ball B used was 0.2 mm, the high-energy ball milling material ratio (mass ratio of powder and grinding ball B) was 1:4, and the high-energy ball milling speed was set to 1300 rpm. After high-energy ball milling for 2 hours, a secondary slurry was obtained;
[0056] (4) The obtained secondary slurry was dried at 90° C., ground through a 60-mesh sieve, and then calcined at 1150° C. for 2 h to obtain the barium titanate powder in this example.
[0057] The preparation method in this example first uses a sand mill to perform preliminary grinding and dispersion of the titanium source and the barium source, then forms uniform barium titanate micronuclei through hydrothermal treatment, and then obtains a powder with smaller particle size, more uniform dispersion, and more barium titanate micronuclei through high-energy ball milling. Finally, barium titanate powder with uniform particle size, good dispersion, high crystallinity, and high tetragonal phase content is prepared through drying, screening, and calcination.
[0058] Embodiments 2 to 5
[0059] The preparation methods of barium titanate powder in Examples 2 to 5 differ from those in Example 1 only in that the sand milling speed in step (1) is different, as shown in Table 1.
[0060] Embodiments 6 to 9
[0061] The preparation methods of barium titanate powder in Examples 6 to 9 differ from those in Example 1 only in that the sand grinding time in step (1) is different, as shown in Table 1.
[0062] Embodiments 10 to 11
[0063] The only difference between the preparation methods of barium titanate powder in Examples 10 to 11 and that in Example 1 is that the diameters of the grinding balls A in step (1) are different, as shown in Table 1.
[0064] Embodiments 12 to 13
[0065] The preparation method of barium titanate powder in Examples 12 to 13 is different from that in Example 1 only in that the ratio of abrasive balls in step (1) is different, as shown in Table 1.
[0066] Embodiments 14 to 17
[0067] The only difference between the preparation methods of barium titanate powder in Examples 14 to 17 and that in Example 1 is that the water bath temperature in step (2) is different, as shown in Table 1.
[0068] Examples 18 to 21
[0069] The preparation method of barium titanate powder in Examples 18 to 21 is different from that in Example 1 only in that the insulation time in step (2) is different, as shown in Table 1.
[0070] Embodiments 22 to 25
[0071] The preparation method of barium titanate powder in Examples 22 to 25 is different from that in Example 1 only in that the rotation speed of the high-energy ball mill in step (3) is different, as shown in Table 1.
[0072] Embodiments 26 to 28
[0073] The preparation method of barium titanate powder in Examples 26 to 28 is different from that in Example 1 only in that the high-energy ball milling time in step (3) is different, as shown in Table 1.
[0074] Embodiments 29 to 30
[0075] The only difference between the preparation methods of barium titanate powder in Examples 29 to 30 and that in Example 1 is that the diameters of the grinding balls B in step (3) are different, as shown in Table 1.
[0076] Examples 31-32
[0077] The preparation method of barium titanate powder in Examples 31 to 32 is different from that in Example 1 only in that the ball ratio of the high-energy ball mill in step (3) is different, as shown in Table 1.
[0078] Comparative Examples 1-2
[0079] The preparation method of barium titanate powder in Comparative Examples 1-2 is different from that in Example 1 only in that the sand milling speed in step (1) is different, as shown in Table 1.
[0080] Comparative Examples 3-4
[0081] The preparation method of barium titanate powder in Comparative Examples 3 to 4 is different from that in Example 1 only in that the sand grinding time in step (1) is different, as shown in Table 1.
[0082] Comparative Examples 5-6
[0083] The preparation method of barium titanate powder in Comparative Examples 5 to 6 is different from that in Example 1 only in that the ratio of abrasive balls in step (1) is different, as shown in Table 1.
[0084] Comparative Example 7
[0085] The method for preparing barium titanate powder in this example is different from that in Example 1 only in that the water bath temperature in step (2) is different, as shown in Table 1.
[0086] Comparative Example 8
[0087] The preparation method of barium titanate powder in this example is different from that in Example 1 only in that an oil bath is used for heating in step (2), and the oil bath temperature is 110° C., as shown in Table 1.
[0088] Comparative Examples 9 to 10
[0089] The preparation method of barium titanate powder in Comparative Examples 9 to 10 is different from that in Example 1 only in that the insulation time in step (2) is different, as shown in Table 1.
[0090] Comparative Examples 11-12
[0091] The preparation method of barium titanate powder in Comparative Examples 11 to 12 is different from that in Example 1 only in that the rotation speed of the high-energy ball mill in step (3) is different, as shown in Table 1.
[0092] Comparative Examples 13-14
[0093] The preparation method of barium titanate powder in Comparative Examples 13 to 14 is different from that in Example 1 only in that the high-energy ball milling time in step (3) is different, as shown in Table 1.
[0094] Comparative Examples 15-16
[0095] The preparation method of barium titanate powder in Comparative Examples 15 to 16 is different from that in Example 1 only in that the ball ratio of the high-energy ball mill in step (3) is different, as shown in Table 1.
[0096] Comparative Example 17
[0097] The preparation method of barium titanate powder in this example is different from that in Example 1 only in that the preparation method in this example does not include the sand grinding step in step (1), and the process parameters of other steps are shown in Table 1.
[0098] Comparative Example 18
[0099] The preparation method of barium titanate powder in this example is different from that in Example 1 only in that the preparation method in this example does not include the water bath insulation step in step (2), and the process parameters of other steps are shown in Table 1.
[0100] Comparative Example 19
[0101] The preparation method of barium titanate powder in this example is different from that in Example 1 only in that the preparation method in this example does not include the high-energy ball milling step in step (3), and the process parameters of other steps are shown in Table 1.
[0102] Comparative Example 20
[0103] The preparation method of barium titanate powder in this example is different from that in Example 1 only in that the preparation method in this example does not include the water bath insulation step in step (2) and the high-energy ball milling step in step (3), and the process parameters of other steps are shown in Table 1.
[0104] Table 1 Process parameters of the preparation methods in Examples 1 to 32 and Comparative Examples 1 to 20
[0105]
[0106]
[0107]
[0108] Performance Test:
[0109] The c / a value and particle size D of the barium titanate powders prepared in Examples 1 to 32 and Comparative Examples 1 to 20 were tested respectively. 50 , specific surface area, average particle size and particle size distribution data. The specific test methods are as follows:
[0110] a)c / a value
[0111] Standard: c / a>1.0100
[0112] Test method: Use an X-ray diffractometer to test the crystal structure of the powder, obtain the X-ray diffraction spectrum, and calculate c / a. The c / a value refers to the ratio of the a-axis length (a) to the c-axis length (c) of the barium titanate lattice constant, that is, the lattice constant ratio c / a.
[0113] b) Particle size D of barium titanate powder 50
[0114] Standard: D 50 <0.700μm
[0115] Test method: Add an appropriate amount of barium titanate powder to the sodium hexametaphosphate aqueous solution, disperse it ultrasonically for 2 minutes, and measure the test solution using a particle size distribution analyzer.
[0116] c) Specific surface area
[0117] Standard: 5.0~6.3m 2 / g
[0118] Test method: The BET method was used to characterize the specific surface area of the prepared powder. The specific method was to measure it by N2 physical adsorption at 77K and obtain the specific surface area from the adsorption isotherm.
[0119] d) Average particle size
[0120] Standard: 200~250nm
[0121] Test method: Measure the powder particles in the SEM image and take the average size of 200 powder particles.
[0122] e) Particle size distribution
[0123] Standard: Particle size distribution <37.0%
[0124] Test method: Particle size distribution = standard deviation / average particle size. Measure the SEM image of the prepared powder to obtain the particle size data of the powder. Then divide the standard deviation by the average value to obtain the particle size distribution. The smaller the particle size distribution value, the better the particle uniformity of the powder.
[0125] Note: The specific surface area and average particle size are mainly affected by calcination. In the present invention, the specific surface area and the powder particle size are kept basically consistent while controlling the same calcination parameters to compare the effects of sand milling, high-energy ball milling and water bath process parameters on the performance. If the specific surface area and the average particle size of the barium titanate powder need to be adjusted, they can be controlled by adjusting the calcination parameters.
[0126] The performance data of the barium titanate powders prepared in Examples 1 to 32 and Comparative Examples 1 to 20 measured by the above test method are shown in Table 2 below.
[0127] Table 2 Performance data of barium titanate powders prepared in Examples 1 to 32 and Comparative Examples 1 to 20
[0128]
[0129]
[0130] It can be seen from Table 2 that by comparing Examples 1 to 5 and Comparative Examples 1 to 2, when the sand milling speed is too low, the mechanical shear force provided by the sand mill is weakened, resulting in a poor sand milling effect on the powder, a slow decrease in particle size, and a large particle size of the powder after sand milling, which is not conducive to obtaining a barium titanate powder with a high c / a value and uniform particles; when the sand milling speed is too high, the mechanical shear effect is too strong, resulting in a small particle size of the powder sand milling, an increase in surface energy, and the raw materials are easily agglomerated again, and the dispersion effect is poor, which is not conducive to obtaining a barium titanate powder with uniform particle size.
[0131] By comparing Examples 6 to 9 and Comparative Examples 3 to 4, it can be seen that when the sand milling time is too short, the mechanical shear force provided by the sand milling is weakened, resulting in a larger particle size of the powder after sand milling, a lower c / a value of the calcined powder, and more serious agglomeration; when the sand milling time is too long, the particle size of the powder after sand milling is too small, the surface energy of the particles increases, the raw materials are prone to agglomeration, the dispersion effect deteriorates, and the particle uniformity of the obtained barium titanate powder is reduced.
[0132] By comparing Examples 12 to 13 and Comparative Examples 5 to 6, it can be seen that when the grinding material-ball ratio is too large (i.e., more material and fewer balls), the collision frequency of the grinding ball A during the sanding process is reduced, the mechanical shear effect is reduced, and the sanding efficiency is low, resulting in a larger sanding particle size of the raw material and uneven dispersion within the same sanding time, which is not conducive to obtaining a barium titanate powder with a high c / a value and uniform particles; when the grinding material-ball ratio is too small (i.e., more material and fewer balls), due to the high sanding efficiency, the raw material particle size is smaller under the same sanding time, the surface energy of the particles is increased, the raw materials are easily agglomerated, the dispersion effect is poor, and it is not conducive to obtaining a barium titanate powder with uniform particle size.
[0133] By comparing Examples 14 to 17 and Comparative Examples 7 to 8, it can be seen that when the temperature of the hydrothermal insulation is too low, it is not conducive to the formation of barium titanate micronuclei, resulting in too few barium titanate micronuclei in the powder, which is not conducive to obtaining barium titanate powder with a high c / a value; when the temperature of the hydrothermal insulation is too high, due to the excessively fast generation rate of the barium titanate micronuclei, it is difficult to form uniformly distributed barium titanate micronuclei with uniform size, and it will cause particles with smaller particle size to agglomerate, resulting in poor particle uniformity and serious agglomeration of the obtained barium titanate powder.
[0134] By comparing Examples 18 to 22 and Comparative Examples 9 to 10, it can be seen that when the hydrothermal insulation time is too short, it is not conducive to the formation of barium titanate micronuclei, resulting in too few barium titanate micronuclei in the powder, which is not conducive to obtaining barium titanate powder with a high c / a value; when the hydrothermal insulation time is too long, it leads to an increase in the degree of agglomeration between particles with smaller particle sizes, and the dispersion uniformity becomes worse, which is not conducive to obtaining barium titanate powder with uniform particle size.
[0135] By comparing Examples 22 to 25 and Comparative Examples 11 to 12, it can be seen that when the rotation speed of the high-energy ball mill is too slow, the mechanical shear force provided is weakened, and the raw material agglomeration occurring during the hydrothermal treatment process cannot be opened, resulting in a deterioration in the dispersion effect of the powder raw materials, a more serious agglomeration of the barium titanate powder, and poor particle uniformity; when the rotation speed of the high-energy ball mill is too fast, the ball milling effect is enhanced, the particle size of the raw materials is reduced, and the surface energy of the particles is increased, resulting in an increase in the degree of agglomeration between particles with smaller particle sizes, deterioration in dispersion uniformity, and a decrease in the c / a value of the barium titanate powder.
[0136] By comparing Examples 26 to 28 and Comparative Examples 13 to 14, it can be seen that when the high-energy ball milling time is too short, the raw material agglomeration that occurs during the hydrothermal treatment process cannot be opened, resulting in a poor dispersion effect of the powder raw materials, which is not conducive to obtaining barium titanate powder with a high c / a value and good dispersibility; when the high-energy ball milling time is too long, the ball milling effect is enhanced, the raw material particle size is reduced, and the surface energy of the particles is increased, resulting in an increase in the degree of agglomeration between particles with smaller particle sizes, poor dispersion uniformity, a reduced c / a value of the barium titanate powder, poor particle uniformity, and severe agglomeration.
[0137] By comparing Examples 31 to 32 and Comparative Examples 15 to 16, it can be seen that when the material-to-ball ratio of the high-energy ball mill is too large (i.e., more material and fewer balls), the collision frequency of the grinding ball B during the grinding process is reduced, the mechanical shear effect is reduced, the ball milling effect is deteriorated, the raw material agglomeration effect is not improved, the c / a value of the obtained barium titanate powder is reduced, and the particle uniformity is deteriorated; when the material-to-ball ratio of the high-energy ball mill is too small (i.e., more balls and less material), the ball milling effect is enhanced, the particle size of the raw material is significantly reduced, and the surface energy of the particles increases rapidly, resulting in an increased degree of agglomeration between particles with smaller particle sizes and poor dispersion uniformity, which is not conducive to obtaining barium titanate powder with uniform particle size.
[0138] It can be seen from Comparative Example 17 that when the preparation method does not contain the sand grinding step in step (1), due to the large particle size and poor dispersibility of the raw materials, uniformly dispersed barium titanate micronuclei cannot be formed during hydrothermal insulation. After high-energy ball milling, the powder particle size is large and the dispersibility is poor, resulting in a low c / a value of the obtained barium titanate powder, poor particle uniformity, and severe agglomeration.
[0139] It can be seen from Comparative Example 18 that when the preparation method does not contain the hydrothermal insulation step in step (2), a large number of uniformly dispersed barium titanate micronuclei cannot be formed, resulting in a reduced c / a value of the barium titanate powder and poor particle uniformity.
[0140] It can be seen from Comparative Example 19 that when the preparation method does not contain the high-energy ball milling step in step (3), the raw materials agglomerate with each other after hydrothermal insulation, resulting in poor dispersion uniformity, resulting in poor particle uniformity of the barium titanate powder after calcination.
[0141] It can be seen from Comparative Example 20 that when the preparation method does not contain the hydrothermal insulation step and the high-energy ball milling step, since there are no uniformly dispersed barium titanate micronuclei in the raw materials, the c / a value of the barium titanate powder is reduced and the particle uniformity is poor.
[0142] In summary, the present invention first uses sand milling to activate the barium source and the titanium source to improve the reaction activity; then the mixed slurry of the barium source and the titanium source after sand milling activation is treated by water bath heating to introduce barium titanate micronuclei on the surface of the barium source; and then the strong mechanical shear force of high-energy ball milling is used to further improve the dispersion and uniformity of the micronuclei and raw materials in the slurry, thereby achieving uniform growth of barium titanate grains during the calcination process, and finally obtaining ultrafine barium titanate powder with uniform grains and high tetragonal phase content, which meets the raw material usage requirements for the production of miniaturized high-end MLCC products.
[0143] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing barium titanate powder, characterized in that: The following steps are involved: S1: grinding the raw materials including the barium source, the titanium source and the solvent with a grinding ball A at a grinding speed of 600 to 1000 rpm for 15 to 30 hours to obtain a primary slurry; S2: heating the primary slurry to 40-100° C. and keeping the temperature for 2-10 hours; S3: high-energy ball milling at a speed of 1000-1400 rpm for 0.5-3 h using grinding ball B to obtain a secondary slurry; S4: calcining the secondary slurry to obtain the barium titanate powder; In the step S1, the ratio of the total mass of the barium source and the titanium source to the mass of the grinding ball A is 1:(1-6); In the step S3, the ratio of the total mass of the barium source and the titanium source to the mass of the grinding ball B is 1:(3-6).
2. The method for preparing barium titanate powder according to claim 1, characterized in that: The diameter of the grinding ball A is 0.3-1.0 mm; And / or, the diameter of the grinding ball B is 0.1-0.5 mm.
3. The method for preparing barium titanate powder according to claim 1, characterized in that: The molar ratio of barium in the barium source to titanium in the titanium source is (0.99-1.04):
1.
4. The method for preparing barium titanate powder according to claim 1, characterized in that: The preparation raw materials also include a dispersant; The mass of the dispersant is 1 to 10% of the total weight of the barium source and the titanium source.
5. The method for preparing barium titanate powder according to claim 1, characterized in that: The step S4 is: drying the secondary slurry, sieving it, and then calcining it to obtain the barium titanate powder.
6. The method for preparing barium titanate powder according to claim 1 or 5, characterized in that: The calcination temperature is 1000-1300° C.; and / or the calcination time is 0.5-3 hours.
7. The method for preparing barium titanate powder according to claim 5, characterized in that: The drying temperature is 80-100°C; And / or, the drying time is 1 to 3 hours.
8. The method for preparing barium titanate powder according to claim 1, characterized in that: The step S2 is heated by water bath.
9. A multilayer ceramic capacitor comprising inner electrode layers and dielectric layers alternately stacked, characterized in that: The dielectric layer is made from raw materials including barium titanate powder obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the method for preparing barium titanate powder according to any one of claims 1 to 8 in preparing ceramic products.
Citation Information
Cited By
Adjustable electromagnetic direct-drive ball rod mill
CN120169495A